"What do you mean it doesn't fit?" - Facility and operational considerations for next-generation forensic imaging equipment. (September 2021) - Knorr, Chris; Adolphi, Natalie L.; Nolte, Kurt B.
Highlights: Successfully installing and utilizing next-generation imaging equipment requires advanced planning and teamwork Key design considerations include decedent movement through the facility, equipment requirements, and safety Collaboration between the end-user, design professionals, and the imaging equipment provider is critical for successful implementation Abstract: The successful integration of next-generation imaging technologies (full body X-ray, CT, and MRI) into the practice of death investigation requires their successful physical incorporation into the autopsy laboratory. A careful analysis of the physical movement of decedents and personnel through the facility is a critical planning step. Other key considerations include the installation and operating requirements of the imaging equipment (including space, clearance, and utilities) and safety requirements (such as shielding and biosafety). Collaboration between laboratory design professionals and medicolegal death investigative personnel can ensure a laboratory design that optimizes function, efficiency, and safety for using imaging technology.